2013
DOI: 10.1002/jsfa.6190
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between polyphenol oxidase activity and nutrition, maturity and quality parameters in flat peach

Abstract: High fertilisation doses resulted in greater yields, but also with higher PPO activity, which is detrimental for the commercial chances of the fruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Although N did not affect the sensory attributes of the fruit at harvest, future work should take into account its effect on the storage potential of the produced fruits. Pascual et al (2013) observed that the N/Ca ratio in peach fruit is the variable that best correlates with the polyphenol oxidase enzyme (PPO), and the increase in the activity of this enzyme reduces the storage capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although N did not affect the sensory attributes of the fruit at harvest, future work should take into account its effect on the storage potential of the produced fruits. Pascual et al (2013) observed that the N/Ca ratio in peach fruit is the variable that best correlates with the polyphenol oxidase enzyme (PPO), and the increase in the activity of this enzyme reduces the storage capacity.…”
Section: Resultsmentioning
confidence: 99%
“…It has direct effect on vegetative growth, yield and fruit quality, therefore the setting of the dose is necessary to ensure the best nutritional balance, replacing the exported quantity and maintaining the proportion between vegetative and reproductive growth. In addition to the dose, application times and the managements adopted in the culture can also affect the response of the applied nitrogen (Dolinski et al 2005;Jia et al 2006;Dolinski et al 2007;Brunetto et al 2007;Ernani et al 2008;Cuquel et al 2011;Falguera et al 2012;Olivos et al 2012;Pascual et al 2013;Souza et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen stress often results in a decrease in plant biomass, leaf nitrogen content, chlorophyll content, and photosynthetic rate of different varieties of olives [ 28 ]; similar results have previously also been found in apple [ 6 ], rice [ 9 ], wheat [ 29 ], and soybean [ 1 ]. In addition to the dose, the application times and management adopted in the culture can also affect the availability of the applied N [ 30 , 31 ]. There were significant differences in the sensitivity of plants to N fertilizer at different developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…N affects vegetative growth, productivity and fruit quality directly (Falguera et al 2012;Olivos et al 2012;Pascual et al 2013;Ferreira et al 2018;Dolinski et al 2018). However, the right dose must be defined so as to ensure nutritional balance of plants and keep their ratio of vegetative and productive growth.…”
Section: Introductionmentioning
confidence: 99%